Medios digitales como recurso didáctico para fortalecer el aprendizaje de inglés en los estudiantes de séptimo grado en la unidad educativa del milenio Bernardo Valdivieso en el periodo 2017-2018. - Lara Carrera, Fernando Joel (2018)
The research: DIGITAL MEDIA AS A TEACHING RESOURCE TO STRENGTHEN ENGLISH LEARNING IN SEVENTH GRADUATE STUDENTS IN THE MILLENIAL EDUCATIONAL UNIT BERNARDO VALDIVIESO IN THE PERIOD 2017-2018., Its general objective was: To apply digital didactic resources through the implementation of videos to strengthen the learning of English in the students of the seventh grade in the Educational Unit of the Millenium Bernardo Valdivieso in the period 2017-2018. Type of study: descriptive, correlational and explanatory; the methods: scientific observation, experimental, deductive, inductive, historical, analytical, dialectical, statistical. Techniques: the interview, the survey, the written test and the checklist; instruments: questionnaire and checklist; the procedure: diagnosis, theoretical foundation, design, application and evaluation of the proposal; achieving the strengthening of English learning in the 22 students of the seventh "A". It is concluded that, using digital media as a didactic resource, the learning of English is strengthened.